Oxidative Stress and Neonatal Respiratory Extracorporeal Membrane Oxygenation - Raffaeli, Genny; Ghirardello, Stefano; Passera, Sofia; Mosca, Fabio; Cavallaro, Giacomo (Frontiers in Physiology, 2018)
Oxidative stress is a frequent condition in critically ill patients, especially if exposed to extracorporeal circulation, and it is associated with worse outcomes and increased mortality. The inflammation triggered by the contact of blood with a non-endogenous surface, the use of high volumes of packed red blood cells and platelets transfusion, the risk of hyperoxia and the impairment of antioxidation systems contribute to the increase of reactive oxygen species and the imbalance of the redox system. This is responsible for the increased production of superoxide anion, hydrogen peroxide, hydroxyl radicals, and peroxynitrite resulting in increased lipid peroxidation, protein oxidation, and DNA damage. The understanding of the pathophysiologic mechanisms leading to redox imbalance would pave the way for the future development of preventive approaches. This review provides an overview of the clinical impact of the oxidative stress during neonatal extracorporeal support and concludes with a brief perspective on the current antioxidant strategies, with the aim to focus on the potential oxidative stress-mediated cell damage that has been implicated in both short and long-term outcomes.